ANALISA VARIABEL-VARIABEL YANG MEMPENGARUHI PROFITABILITY NET MARGIN - Dra. Rr. Sri Diniarti, S.E. (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
This research is an explanatory research, because it explaining about the relationship among the hypnotized variables. This research aims to knowing about the relationship and the influence between the accounts, location to the other bank, and loans to the net margin in Bank Jatim Madiun. The results are between accounts to net margin has positive relationship, between location to another bank to net margin has negative relationship, and between loans to net margin has positive relationship. Together, the variables have strong enough relationship to net margin, it showing by coefficient of determination value is 0,956, it means that the value close to 1. So, 4,4% of Profitability Net Margin influenced by the others variables.The method of research was by using field research that including observation, interview and library research.The analyzing data method was by using Multiple Regression Analysis, Correlation Analysis, and Coefficient of Determination Analysis.